Photocatalytic activity improvement and application of UV-TiO2 photocatalysis in textile wastewater treatment: A review - Al-Mamun, M.R.; Kader, S.; Islam, M.S.; Khan, M.Z.H. (Journal of environmental chemical engineering, 2019)
Photocatalytic degradation of dye and phenolic compounds as textile effluent using UV- TiO2 photocatalysis based on color removal. [Display omitted] •TiO2 is used as a semiconductor photocatalyst in presence of UV light.•TiO2 photocatalytic advanced oxidation process is executed by five steps.•Metal and non-metal co-doping on TiO2 can increase photocatlytic performance.•UV- doped TiO2 photocatalysis is able to mineralize toxic dyes and phenolic compounds. Treatment of textile wastewater using titanium dioxide (TiO2) photocatalysis has been started from the last decade and reached attention to the researchers because of its versatile application. The variety of applications of TiO2 as a photocatalyst has been taken place because of low operating temperature, biologically inert nature, low energy consumption, water insolubility, ease availability and photoactivity, less toxicity, high chemical stability, suitable flat band potential, narrow band gap and environmentally benign. The successful and efficient application of photocatalysis depends on quality of photocatalyst, nature of pollutants, and source of light, which should be in close contact with each other. The TiO2 photocatalyst is used for the effluent treatment of textile wastewater in the presence of ultraviolet (UV) irradiation. Heterogeneous UV-TiO2 photocatalysis is capable to remove organic pollutants from textile wastewater, which has been widely studied and the technology also being commercialized in many developing countries in the world. This review focuses on the mechanism of UV-TiO2 photocatalysis, modification of TiO2 photocatalyst, and application of doping and co-doping in order to improve the photocatalytic activity in wastewater treatment. In addition, the review conveys comprehensive and fundamental assessments of the photocatalytic activity for the removal of organic dyes and phenolic compounds from textile wastewater.